Quantum squeezing for Dirac fields - Dhungel, Prem Raj; Sharma, Sanat Kumar; Khanal, Uday Raj (Scientific World, 2025)
Squeezing of Dirac field with expansion of the universe is analysed for its dependence on the scale factor. It is found to peak at a time, and also develops a local minimum for some combinations of k, M and other parameters, indicating possibilities of structure formation. Also, the local minimum could indicate effects that could account for some of the dark matter.